PRODUCTION CHAINS IN THE TEXTILE SECTOR: AN ANALYSIS OF LABOR LIABILITY IN CASES OF OUTSOURCING AND SUBCONTRACTING (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Outsourcing, as a legal and economic phenomenon arising from business de-verticalization and the pursuit of greater productive efficiency, has been widely adopted as a strategy for cost reduction and business activity reorganization. Currently, outsourcing produces profound impacts on global production chains, especially in the textile sector, where the search for efficiency and cost reduction has led to intense subcontracting. This has resulted in the intensification of labor precarization, chain subcontracting, and the difficulty of assigning responsibility for violations of fundamental rights. In this context, the present study aims to analyze outsourcing in the textile sector and its impacts on workers’ dignity, particularly due to the precariousness of labor rights. To this end, the deductive method will be employed, using bibliographic and jurisprudential research, with the analysis of academic articles, specialized legal doctrine, current normative precepts, and relevant case law from the Superior Labor Court (TST) and the Federal Supreme Court (STF).